Trends in twenty-first century African theatre and performance - Igweonu, Kenechukwu, 1975-; International Federation for Theatre Research. African Theatre and Performance Working Group (Amsterdam ; New York, NY : Rodopi, 2011)
"A collection of regionally focused articles on African theatre and performance. The volume provides a broad exploration of the current state of African theatre and performance and considers the directions they are taking in the 21st Century. It contains sections on current trends in theatre and performance studies, on applied/community theatre and on playwrights. The chapters have evolved out of a working group process, in which papers were submitted to peer-group scrutiny over a period of four years, at four international conferences. The book will be particularly useful as a key text for undergraduate and postgraduate courses in non-western theatre and performance (where this includes African theatre and performance), and would be a very useful resource for theatre scholars and anyone interested in African performance forms and cultures."--Back cover.
"IFTR / FIRT; African Theatre and Performance Working Group."
Includes bibliographical references.
Description based on print version record.
Keywords: African drama -- 21st century -- History and criticism; Theater -- Africa -- 21st century; PERFORMING ARTS / Theater / History & Criticism; Electronic books